Exploring Environmental Health Determinants and Their Influence on Childhood Stunting - Baren Yoel Hindom; Indasah; Agusta Dian Ellina (Health and Technology Journal (HTechJ), 2025)
Stunting remains a significant public health issue in Indonesia, particularly in the eastern provinces such as West Papua, where environmental and infrastructural limitations exacerbate child health disparities. Environmental health factors—such as water quality, sanitation, and hygiene behaviors—are recognized as crucial yet underexplored determinants of stunting. This study aimed to investigate the role of environmental health conditions and community practices in contributing to stunting among children under five in the working area of Degen Public Health Center, Teluk Patipi District, Fakfak Regency, West Papua Province. A qualitative descriptive design was employed to capture the lived experiences and perceptions of mothers, health cadres, and local health officers. Data were collected from January to March 2025 through semi-structured interviews, direct observation, and a brief descriptive survey involving 66 mothers of children under the age of five. Thematic content analysis was conducted following Braun and Clarke's framework, supported by descriptive statistics to summarize demographic and stunting-related characteristics. The findings revealed four major themes influencing stunting: (1) limited access to safe water and proper sanitation facilities; (2) inadequate household waste management; (3) poor hygiene behaviors influenced by cultural practices and limited awareness; and (4) insufficient community-based health education. Quantitative data indicated that more than half of the children exhibited stunted growth, primarily in households lacking access to clean water and sanitary latrines. Environmental health factors significantly contribute to the persistence of stunting in rural Papua settings. Strengthening water, sanitation, and hygiene (WASH) infrastructure, along with culturally tailored community health education, is essential for reducing stunting prevalence and improving child health outcomes.